Consumo de frutas - verduras y estado nutricional en adjudicatarios del mercado municipal Gran Colombia de la ciudad de Loja - Vuele Sinche, Mayra Elizabeth (2023)
The World Health Organization (WHO) recommends the consumption of 5 daily servings of fruits and vegetables, because of it contributes to the prevention of cardiovascular diseases (arterial hypertension, heart failure) and some types of cancers. The objective of the Titulation Work consisted to determine the consumption of fruits and vegetables and the nutritional status in the beneficiaries of the Gran Colombia municipal market in the city of Loja. It was a relational study, with a quantitative approach, cross-sectional cohort. The population consisted of 270 individuals. The instrument to evaluate nutritional status was the body mass index and for the amount of fruit and vegetable consumption, the questionnaire of the scientific research "Consumption of fruits and vegetables among university students in Denmark" was used, translated and adapted for this study. The results of the study showed that 53.7% of the respondents ingested 1 portion of fruits and vegetables per day, 43% were overweight and 26.3% were obese grade I; more than half of the participants ate raw fruits without additions, i.e. 63%; and vegetables as raw vegetables, 64.1%; the chi-square determined that there was no relationship between consumption of fruits (0.067) and vegetables (0.084) and nutritional status. It is concluded that the allottees did not eat the portions of fruits and vegetables recommended by the WHO, more than half of them are overweight and class I obese, and in this population there was no relationship between fruit-vegetable consumption and nutritional status